MAKNA KALIMAT PERINTAH DALAM AL-QUR’AN SURAT YUSUF - Muhammad Ichsan Haikal; Nur Raudhatul Jannah (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2021)
s meaning and purpose in Surah Yusuf. This study uses a qualitative descriptive method that describes the existing data. The data is obtained from the verses of Surah Yusuf which contains a command sentence (amr). The results of this study indicate that in Surah Yusuf there are commands or amr sentences as many as 32 data contained in the verse, namely in verses 9 (2), 10, 12, 21, 23, 29 (2), 31, 36, 42, 43 , 46, 50 (2), 54, 55, 59, 62, 63, 67, 78, 81 (2), 82, 87, 88, 93, 97, 99, 101 and 108. Of the 32 data, there are 31 data the form belongs to the form of fi'il amr and 1 data belongs to the form of isim fi'il amr which is contained in verse 23. Meanwhile, of the 32 command sentences there are 19 which mean an essential command, besides that there are some deviations in the meaning of the command sentence (amr). In Surah Yusuf, the meaning of irshad is found in verses 29, 50 and 67, the meaning of takhyir is found in verse 9 and the meaning of prayer or request is found in verses 12, 55, 63, 78, 88, 97 and 101.